Pengaruh Teman Sebaya dan Persepsi Pola Asuh Orang Tua Terhadap Agresivitas Siswa di Sekolah Dasar Gugus Sugarda - Sulistiyowati Budikuncoroningsih (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2017)
This research was motivated by the existence of many students' aggressiveness problems. This research is aimed at finding out: 1) the influence of peers on students' aggressiveness; 2) the influence of parenting pattern on students' aggressiveness; 3) the influence of peers and perception of parenting pattern on students' aggressiveness. Quantitative approach with descriptive correlation was used as the research method. The population in this research was 245 students with 71 samples taken using proportionate stratified random sampling. Questionnaire was used to collect the data. Correlation formula of product moment, multiple correlation, simple regression and multiple regression were used to analyze the data . The result of the data showed that 1) there was a significant influence of peers on students' aggressiveness with the percentage of 12.8%; 2) there was a significant influence of parenting pattern on students' aggressiveness with the percentage of 14.5%; 3) there was a significant influence of peers and parenting pattern on students' aggressiveness with the percentage of 18.8 %.